2022
DOI: 10.31234/osf.io/k7m65
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commonalities Between Mind Wandering and Task Switching: An Event-Related Potential Study

Abstract: Previous research has established that mind wandering does not necessarily disrupt one’s task-switching performance. Here we tested, using event-related potentials (ERPs), the possibility that mind wandering during task switching does not disrupt switching-related mental processes but rather promotes them. In the current study, a final sample of 16 young adults performed a task-switching paradigm while electroencephalography was continuously recorded; mind wandering was assessed via thought probes at the end o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This finding contradicts the typical P3 attenuation observed during mind-wandering episodes. The increased P3 amplitude during higher-order switch trials suggested the involvement of executive control processes in both mind-wandering and task switching, supporting the idea of a connection between attentional switching and mind-wandering [89]. Furthermore, the impact of mind-wandering on the P3 response may not be related to changes in motor activity or general arousal [98].…”
Section: P3 and Attentional Orientation During Mind-wanderingmentioning
confidence: 74%
See 2 more Smart Citations
“…This finding contradicts the typical P3 attenuation observed during mind-wandering episodes. The increased P3 amplitude during higher-order switch trials suggested the involvement of executive control processes in both mind-wandering and task switching, supporting the idea of a connection between attentional switching and mind-wandering [89]. Furthermore, the impact of mind-wandering on the P3 response may not be related to changes in motor activity or general arousal [98].…”
Section: P3 and Attentional Orientation During Mind-wanderingmentioning
confidence: 74%
“…However, Wong et al [89] revealed an unexpected pattern in the P3 amplitude during mind-wandering switch trials where P3 amplitudes were greater than those in the on-task switch trials. This finding contradicts the typical P3 attenuation observed during mind-wandering episodes.…”
Section: P3 and Attentional Orientation During Mind-wanderingmentioning
confidence: 96%
See 1 more Smart Citation